RETAIL PRIVATE LABEL’S STRATEGIES: A CASE STUDY IN A LARGE BRAZILIAN SUPERMARKET CHAIN - SPINELLI,PAULA BULAMAH (2006)
ABSTRACT The present study approaches the advantages and risks related to private labels under a retailers’ perspective, as well as the private label strategies and its growth in the Brazilian market. The paper analyses the strategies used by a large Brazilian supermarket chain with regards to its private labels’ management, using the case study method. The results showed the existence of two private label lines of products, with different strategies: one line of light products (proprietary brand) and another line of products that carry the name of the supermarket under study (retail brand endorsement), both classified as using the fantasy positioning strategy.